The Eunuch and the Baldhead: Sexuality in Early Jewish-Christian Polemic - Rubin, Yiśraʾel Netanʾel (The review of rabbinic Judaism, 2021)
Abstract Defining appropriate attitudes towards sexuality has always been an issue in Jewish-Christian polemic. Contemporary Jewish writers tend to boast of Judaism’s liberal attitude toward sexuality, while medieval Jewish polemicists were defensive when confronting Christian attacks on this matter. In ancient times, when sexual puritanism was less popular, Jewish theologians did not refrain from showing their contempt for the Christian value of celibacy. This article proposes a new reading of the Talmudic legend about an argument between Joshua b. Karhah and a Christian eunuch. In this reading, the Christian figure stands for Origen, a Church father described in Christian sources as having castrated himself owing to a literal interpretation of the New Testament. In this reading, the debate summarizes the Talmudic rabbis’ perspective on the difference between Jewish and Christian views of sexuality.